How individual values and attitude influence consumers’ purchase intention of electric vehicles—some insights from Kuala Lumpur, Malaysia - Rafia, Afroz; Rahman, Mohammed Ataur; Masud, Muhammad Mehedi; Akhtar, Rulia; Duasa, Jarita (Sage Publications, 2015)
This article observes how the individual values and attitudes of consumers in Kuala Lumpur, Malaysia influence their purchase intention of electric vehicles (EVs) using the well-known theory of reasoned action (TRA). This study analyzed the data collected from 200 respondents from Kuala Lumpur, Malaysia. These respondents were asked about their views concerning their value sets, attitudes and purchase intention of EV using the structural equation modelling (SEM) technique. Findings of this study indicate that individual consequences relating to cost and convenience of consumers is negatively related to intention to purchase EVs. Environmental consequences are not a significant predictor of purchase intention. Conservation value was found to be positively related to the attitude of the respondents on environmental consequences but less intensely with individual consequences, while both selftranscendence value and self-enhancement value were positively related to individual consequences. Individual consequences and self-enhancement values were negatively related to environmentally responsible purchase intention. This article shows that the extended TRA might be applicable to the Malaysian context. The results of the study also suggest that domestic and foreign manufacturers of EVs should also take into consideration the perceptible easiness and convenience of users to recycle and reuse battery by using special materials that are recyclable and not harmful to the users.